Improvement in cognitive impairment following a 12‐week aerobic exercise intervention in individuals with non‐cirrhotic chronic hepatitis C. Issue 4 (26th January 2021) - O'Gorman, Philip; Strahan, Orla; Ferguson, Damien; Monaghan, Ann; Kennedy, Megan; Forde, Cuisle; Melo, Ashanty M.; Doherty, Derek G.; O'Brien, Kelly K.; McKiernan, Susan; Kenny, Rose Anne; Coen, Robert; et al.
Abstract: Cognitive impairment occurs in 30%–50% of patients with non‐cirrhotic chronic hepatitis C virus (HCV) infection. Exercise is beneficial in preventing and treating cognitive impairment and cardiometabolic abnormalities in many chronic inflammatory diseases, but there are few studies investigating the impact of exercise in HCV infection. The study aimed to assess the effect of a 12‐week aerobic exercise intervention on cognition and extrahepatic manifestations in individuals with HCV. In this nonrandomized controlled pilot study, individuals with HCV participated in a 12‐week aerobic exercise intervention. Outcome measures included cognition (Montreal Cognitive Assessment [MOCA], Trail Making Test A & B [TMT‐A; TMT‐B], Digit Symbol Test [DST]), cardiorespiratory fitness (estimated V ˙ O 2 max ), physical activity (accelerometry), anthropometry, quality of life (depression; fatigue; sleep quality) and biochemical markers. Outcomes were assessed at baseline (T0), intervention completion (T1) and 12 weeks after intervention completion (T2). Thirty‐one patients completed the study (exercise group n = 13, control group n = 18). In the exercise group, cognition improved at T1 in the TMT‐A (31% mean improvement, p = 0.019), TMT‐B (15% mean improvement, p = 0.012) time and MOCA (14% mean improvement, p ≤ 0.001). These improvements were not maintained at T2. Depression ( p = 0.038), sleep quality ( p = 0.002), fatigue ( p = 0.037) and estimated V ˙ O 2 max (7.8 mL kg −1 min −1 [22%] mean increase, p = 0.004) also improved at T1. In conclusion, this study demonstrates the benefits of a 12‐week aerobic exercise intervention in improving cognition, quality of life and cardiorespiratory fitness in individuals with HCV. Larger studies are needed to confirm these findings and strategies for continued exercise engagement in individuals with HCV are warranted for sustained benefits.